REPRESENTATION OR MISREPRESENTATION OF AUTISTIC AGENCY? MULTIMODAL LITERACY ANALYSIS OF MAKAYLA’S VOICE - Sari, Artanti Puspita (Jurnal Ilmiah Bina Bahasa, 2025)
While media portrayals of autism have been widely studied, limited research has examined how the agency of non-speaking autistic individuals is constructed through multimodal storytelling and mediated communication. This study examines how nonverbal autistic agency is portrayed in the Netflix documentary "Makayla’s Voice: A Letter to the World." Grounded in multimodal literacy theory, the study employs qualitative methods and thematic analysis to examine how the film frames Makayla’s communication and self-representation across text, audio, and visual modes. The analysis also draws on agency theory to examine how autistic agency is represented, and it applies the social model of disability to explore how the film challenges or reinforces societal discriminatory attitudes toward autism. Findings reveal a complex portrayal: the film affirms Makayla’s agency through poetic narration, metaphor, and visual imagery, yet simultaneously mediates her voice through facilitator involvement and selective editing. These strategies contribute to a process of narrative idealization, in which a story is smoothed over to enhance a character’s positive qualities. The study contributes to critical literacy by demonstrating how media can both empower and constrain the voices of non-speaking autistic individuals. It also calls for more nuanced and ethically grounded representations that recognize diverse communicative practices and multimodal literacies.